Health and healing - Weil, Andrew (Houghton Mifflin, 1998)
In light of the health care crisis and the proliferation of HMOs, Dr. Weil has written a new introduction to this groundbreaking study of conventional and alternative medicine. Health and Healing presents the spectrum of alternative healing practices - holistic medicine, homeopathy, osteopathy, chiropractic, Chinese medicine - and outlines how they differ from conventional medicine.